2011
DOI: 10.1080/08832323.2010.510153
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Knowledge Sharing and Conversation Interaction Impact on Grade in an Online Business Course

Abstract: Student knowledge sharing and conversation theory interactions were coded from asynchronous discussion forums to measure the effect of learning-oriented utterances on academic performance. The sample was 3 terms of an online business course (in an accredited MBA program) at a U.S.-based university. Correlation, stepwise regression, and multiple least squares regression were used to create a statistically significant model with 4 interaction factors that captured 89% of adjusted variance effect on grade. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Therefore this was part of the pedagogy. In a similar fashion, Strang (2011a) found that students improved their learning when they applied conversation theory in a form of group collaboration. He used an online asynchronous forum to facilitate group collaboration outside of the classroom.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Therefore this was part of the pedagogy. In a similar fashion, Strang (2011a) found that students improved their learning when they applied conversation theory in a form of group collaboration. He used an online asynchronous forum to facilitate group collaboration outside of the classroom.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Similarly, Sebastianelli and Tamimi (2011) found that online MBA students rated professor-student interaction to be the most useful feature in learning quantitative content (statistics and management science) online. Sher (2009) found that both types of interaction (instructor to student and student to student) had a significant and positive impact on student learning and satisfaction in online courses from various professional programs (tourism, project management, and health sciences), and Strang (2011) found that higher levels of asynchronous knowledge sharing and conversation theory interactions among students (student-student interaction) improved academic performance (i.e., higher grades) in an online management information systems course.…”
Section: Interaction-related Factorsmentioning
confidence: 97%
“…Over the years, more educational studies have linked students' perceptions of online discussions to participation in AODs (Lee, 2013). Furthermore, there are several studies that support the view that a positive correlation exists among the students' participation (total number of messages posted and total system access) and students' learning achievement measured by end-of-semester grade (Morris, Finnegan, & Sz-Shyan, 2005;Palmer, Holt, & Bray, 2008;Shaw, 2013;Strang, 2011). Generally, active learners in online courses outperform less active learners in their final course grades (Wilson, Pollock, & Hamann, 2007).…”
Section: Introductionmentioning
confidence: 99%